The One-Gate Management System and Temple Conservation: A Comparative Study of Borobudur and Angkor Wat Temples - Wicaksono, Ajie; Fitri, Ebtana Sella Mayang; Anggara, Tio; Sum, Sochenda (Baileo: Jurnal Sosial Humaniora, 2025)
This study aims to analyze the management of Borobudur Temple in Indonesia and Angkor Wat in Cambodia as world heritage sites, focusing on a comparison between single-gate management and conservation-based approaches. The research adopts a qualitative descriptive method, involving data collection through literature review, observation, and interviews. Data analysis is conducted using the Miles and Huberman approach, which includes data reduction, data presentation, and conclusion drawing. The findings reveal that the management of Borobudur Temple has undergone significant transformation, shifting from multi-party management to a single-gate system in 2024 under InJourney Destination Management (IDM). This approach integrates Borobudur as both a tourist destination and a place of worship for Buddhists, with challenges arising in harmonizing conservation and tourism needs. Meanwhile, Angkor Wat has been managed by the APSARA Authority since 1995, with a stronger emphasis on conservation and controlled management to maintain its appeal to tourists while prioritizing the preservation of its cultural and historical values. The study concludes that single-gate management has the potential to enhance efficiency and synergy but requires adaptive strategies to ensure conservation sustainability. The novelty of this research lies in its comprehensive comparison of two management models, offering valuable insights for managing other world heritage sites. The study recommends a more balanced integration of tourism, conservation needs, and local community involvement to support the advancement of social sciences and humanities, particularly in the field of cultural heritage management studies.